New ways of seeing and being: Evaluating an acceptance and mindfulness group for parents of young people with intellectual disabilities who display challenging behaviour. (March 2016) - Reid, Caroline; Gill, Freya; Gore, Nick; Brady, Serena
The current study presents findings from an acceptance and commitment therapy-based intervention for family carers of children who have an intellectual/developmental disability and display high levels of challenging behaviour. The parent well-being workshops consist of two workshops incorporating acceptance and mindfulness-based exercises and discussions. Semi-structured interviews were conducted with five family carers following attendance of the workshops. Participants found the workshops useful and reported that they were better able to cope with stress. They also described how they had incorporated mindfulness into their daily lives and how their practice had had positive effects on their own well-being and on those around them (e.g. their child). Implications of the findings are discussed with emphasis on how the workshops can be included within a positive behaviour support framework. Future directions include a more robust quantitative evaluation, inclusion of follow-up sessions and the application of the workshops with other client groups and in other delivery formats.